Association of core needle biopsy tract resection with local recurrence in extremity soft tissue sarcoma - Siddiqi, Ather; Jede, Felix (Skeletal radiology, 2017)
ObjectiveDue to minimal tissue violation in percutaneous core needle biopsy (CNB), in contrast to open biopsy, the risk of tumor seeding and subsequent local recurrence (LR) along the biopsy tract remains unclear in extremity soft tissue sarcoma (STS). This study sought to examine the association of CNB tract resection on LR in a large STS institutional database.Materials and methodsAfter a retrospective review of the 116 patients who underwent CNB prior to surgery for previously untreated non-metastatic extremity STS, 36 patients who did not have CNB tracts resected (CNB-NR) were matched with 36 who had CNB tracts resected (CNB-R) for the factors that are known to affect LR.ResultsTwo patients (6%) developed LR in the CNB-R group, whereas three patients (8%) developed LR in the CNB-NR group (P = 0.643). On Kaplan-Meier analysis, there was no significant difference in LR-free survival between the two groups (94.3% ± 3.9 for the CNB-R group vs. 93.8% ± 4.3 for the CNB-NR group, P = 0.747).ConclusionOur data suggest any influence of a CNB tract resection on LR, within the limitations of this study, is likely to be of minor clinical importance in extremity STS. Although it would be prudent to resect the CNB tract in most cases, not resecting the CNB tract is a feasible option if identification or removal of the CNB tract proves difficult.